FAKTOR YANG MEMPENGARUHI KUALITAS KERJA KARYAWAN PERBANKAN BUMN DI KOTA BATAM - Gilang Bagus Fadlan; Agustinus Setyawan (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2024)
The main purpose of this study is to determine the factors of work motivation, work facilities, compensation and work environment affect the quality of work of State-Owned Enterprises (SOEs) banking namely PT Bank Rakyat Indonesia, PT Bank Mandiri and PT Bank Negara Indonesia in the city of Batam. This research is descriptive quantitative research in which data collection uses primary data (questionnaires) containing questions about the variables studied. The target population of this study are employees of State-Owned Enterprises (BUMN) banking companies in Batam City such as PT Bank Mandiri, PT Bank Rakyat Indonesia, and PT Bank Negara Indonesia. Then the sample in this study the author set 100 samples using stratified random sampling technique. The results showed that the variables of work motivation, work facilities and compensation do not affect the quality of work. While the work environment variable is the right variable in influencing the quality of work in three State-Owned Enterprises (BUMN) banks PT Bank Mandiri, PT Bank Rakyat Indonesia and PT Bank Negara Indonesia.